2019
DOI: 10.1177/1591019919839196
|View full text |Cite
|
Sign up to set email alerts
|

The Silk Vista Baby: Initial experience and report of two cases

Abstract: In this report, we present two cases using a novel flow diverter, the Silk Vista Baby, to treat aneurysms successfully, both ruptured and unruptured, that would have been difficult to treat using alternative flow diverters. We describe the clinical and radiological features, outcome and the unique features of the Silk Vista Baby flow diverter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Immediately after stent deployment, 8 aneurysms (18.6%) were classified as completely occluded (O'Kelly Marotta grading system [OKM] D), 5 (11.6%) were near complete occlusion (OKM C), 4 (9.3%) showed incomplete filling (OKM B), and 26 (60.4%) showed complete filling (OKM A). Longer term follow-up data are awaited and in the only other available publication regarding the Silk Vista Baby both aneurysms were completely occluded by follow-up [36]. The results of the present study are very similar with similar rates of occlusion when compared to the FRED Jnr (79.2% p48MW vs. 78% FRED Jnr) and similar rates of complication.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Immediately after stent deployment, 8 aneurysms (18.6%) were classified as completely occluded (O'Kelly Marotta grading system [OKM] D), 5 (11.6%) were near complete occlusion (OKM C), 4 (9.3%) showed incomplete filling (OKM B), and 26 (60.4%) showed complete filling (OKM A). Longer term follow-up data are awaited and in the only other available publication regarding the Silk Vista Baby both aneurysms were completely occluded by follow-up [36]. The results of the present study are very similar with similar rates of occlusion when compared to the FRED Jnr (79.2% p48MW vs. 78% FRED Jnr) and similar rates of complication.…”
Section: Discussionsupporting
confidence: 75%
“…It is of note that the authors reported no branch occlusions or significant caliber reductions in the stented vessels although this remains of concern [18, 33,34]. Early results on the Silk Vista Baby device have also recently been published [35,36]. Martinez-Galdámez et al [35] recently reported the results of a multicenter study involving 41 patients (28 female, average age 50.5 years) with 43 aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…We noted an improvement in terms of implant radio-opacity and visibility, which according to our experience facilitates the deployment of the stent itself. The LVIS EVO uses DFT technology to optimise visualisation and is similar in this regard to the Acandis Accero, 20 the Silk Vista Baby [21][22][23] and the p48. 24,25 In our series there was no evidence of incomplete aneurysmal neck coverage or compromised stent/ vessel relationship which is a well-known limitation of braided-cell designed stents.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the main indication is wide-neck unruptured aneurysms arising from the paraclinoid or supraclinoid segments, advancements in FD technology developed in recent years have enabled a broadening of the indications, with treatment in smaller caliber vessels and in distal locations now feasible. [2][3][4][5] One of the main changes to the procedural set-up has been the use of triaxial systems which occurred as a consequence of the fact that nearly all available FDs require the use of 0.027 inch (0.69) microcatheters for the deployment of a device designed for a 4 or 5 mm vessel. [6][7][8] The complexity of the procedure is secondary to vessel tortuosity, where distal navigation of the microcatheter can be cumbersome, requiring robust coaxial constructions, 9 10 or the opening/apposition of the braid may be affected.…”
Section: Introductionmentioning
confidence: 99%